Propositional Logic

Propositions

Propositional Variables

Compound Propositions

Truth Tables

Negation

Conjunction

Disjunction

Exclusive Or

Implication

Converse, Contrapositive, and Inverse

Biconditional

Truth Tables for Compound Propositions

Equivalent Propositions

Precedence of Logical Operators

Operator Precedence
\(\neg\) 1
\(\wedge\) 2
\(\vee\) 3
\(\rightarrow\) 4
\(\leftrightarrow\) 5

Tautologies, Contradictions, and Contingencies

Logic Equivalence

De Morgan’s Laws

Key Logical Equivalences

Identity Laws: \(p \wedge T \equiv p, \quad p \vee F \equiv p\)
Domination Laws: \(p \vee T \equiv T, \quad p \wedge F \equiv F\)
Idempotent Laws: \(p \vee p \equiv p, \quad p \wedge p \equiv p\)
Double Negation Law: \(\neg (\neg p) \equiv p\)
Negation Laws: \(p \vee \neg p \equiv T, \quad p \wedge \neg p \equiv F\)
Commutative Laws: \(p \vee q \equiv q \vee p, \quad p \wedge q \equiv q \wedge p\)
Associative Laws: \((p \wedge q) \wedge r \equiv p \wedge (q \wedge r)\)
\((p \vee q) \vee r \equiv p \vee (q \vee r)\)
Distributive Laws: \((p \vee (q \wedge r)) \equiv (p \vee q) \wedge (p \vee r)\)
\((p \wedge (q \vee r)) \equiv (p \wedge q) \vee (p \wedge r)\)
Absorption Laws: \(p \vee (p \wedge q) \equiv p\)
\(p \wedge (p \vee q) \equiv p\)

Logical Equivalences Involving Conditional Statements

Equivalence Proofs

Equivalence Proof Example

Show that \(\neg (p \vee (\neg p \wedge q))\) is logically equivalent to \(\neg p \wedge \neg q\)

\[\begin{array}{llll} \neg (p \vee (\neg p \wedge q)) & \equiv & \neg p \wedge \neg( \neg p \wedge q) & \text{by De Morgan's law} \\ & \equiv & \neg p \wedge (\neg(\neg p) \vee \neg q) & \text{by De Morgan's law} \\ & \equiv & \neg p \wedge (p \vee \neg q) & \text{by the double negation law} \\ & \equiv & (\neg p \wedge p) \vee (\neg p \wedge \neg q) & \text{by the distributive law} \\ & \equiv & F \vee(\neg p \wedge \neg q) & \text{by the negation law} \\ & \equiv & (\neg p \wedge \neg q) \vee F & \text{by the commutative law} \\ & \equiv & (\neg p \wedge \neg q) & \text{by the identity law} \\ \end{array}\]

Equivalence Proof Example

Show that \((p \wedge q) \rightarrow (p \vee q)\) is a tautology

\[\begin{array}{llll} (p \wedge q) \rightarrow (p \vee q) & \equiv & \neg(p \wedge q) \vee (p \vee q) & \text{by} p \rightarrow q \equiv \neg p \vee q \\ & \equiv & (\neg p \vee \neg q) \vee (p \vee q) & \text{by De Morgan's law} \\ & \equiv & (\neg p \vee p) \vee (\neg q \vee q) & \text{by the associative and} \\ & \vdots & & \text{commutative laws} \\ & \equiv & T \vee T & \text{by the negation law} \\ & \equiv & T & \text{by the domination law} \\ \end{array}\]